2022
DOI: 10.4136/ambi-agua.2816
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, growth and quality of guava seedlings under salt stress and salicylic acid

Abstract: Guava is a popular Brazilian fruit that is widely produced in Northeastern Brazil, a region with water sources that commonly have high concentrations of salts. Thus, searching for techniques that allow the management of these waters is extremely important for the expansion of irrigated agriculture. In this context, salicylic acid is a phytohormone that can contribute to reducing the effects of salt stress on plants. Given the above, this study evaluated the effect of foliar application of salicylic acid at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…There was a significant effect (p<0.01) of irrigation water salinity on the RGR LA from 85 to 125 DAS, with a quadratic response according to the regression equation (Figure 4C), whose highest (0.018 cm 2 cm -2 per day) and lowest (0.012 cm 2 cm -2 per day) values were obtained, respectively, with the ECw levels of 1.1 and 3.5 dS m -1 . The inhibition in the relative growth rate of leaf area in guava seedlings could be associated with the decrease in the number of leaves and leaf area (Figures 2A and 3A), as the reduction of the transpiration surface is a plant adaptation mechanism to reduce transpiration rates and mitigate the stress caused by excess salts (XAVIER et al, 2022). Abrantes et al (2017) observed a decreasing linear effect on the RGR LA with the increase in ECw from 50 to 100 days after emergence, causing a 6.85% decrease per unit increase in ECw.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant effect (p<0.01) of irrigation water salinity on the RGR LA from 85 to 125 DAS, with a quadratic response according to the regression equation (Figure 4C), whose highest (0.018 cm 2 cm -2 per day) and lowest (0.012 cm 2 cm -2 per day) values were obtained, respectively, with the ECw levels of 1.1 and 3.5 dS m -1 . The inhibition in the relative growth rate of leaf area in guava seedlings could be associated with the decrease in the number of leaves and leaf area (Figures 2A and 3A), as the reduction of the transpiration surface is a plant adaptation mechanism to reduce transpiration rates and mitigate the stress caused by excess salts (XAVIER et al, 2022). Abrantes et al (2017) observed a decreasing linear effect on the RGR LA with the increase in ECw from 50 to 100 days after emergence, causing a 6.85% decrease per unit increase in ECw.…”
Section: Resultsmentioning
confidence: 99%
“…Seedlings irrigated with 3.5 dS m -1 showed a 29.44% reduction in DMS compared to those irrigated with the lowest salinity level. The high NaCl concentrations in the root zone possibly increased the uptake of these salts in the mesophyll, decreasing the uptake of other ions, causing toxicity by specific ions, leading to the appearance of physiological and nutritional damage in the crops (XAVIER et al, 2022), and, consequently, affecting biomass production. For the same cultivar, Silva et al (2015) Figure 5B shows that the DMS was lower in plants fertilized with the C4 combination, whereas the C1 combination resulted in a higher DMS increase.…”
Section: Resultsmentioning
confidence: 99%
“…Lima et al (2019), when evaluating gas exchange in castor bean plants as a function of the cationic nature of irrigation water (S1-Control; S2 -Na + ; S3 -Ca 2+ ; S4 -Na + + Ca 2+ ; S5 -K + , and S6 -Na + + Ca 2+ + Mg 2+ ), also observed that, except for waters containing potassium and salinity of 4.5 dS m -1 , caused a decrease in stomatal conductance, regardless of the cationic nature of the water. In another study, Xavier et al (2022) evaluated the gas exchange of 'Paluma' guava seedlings as a function of irrigation with saline waters (ECw: 0.6 to 4.2 dS m -1 ) prepared with Na + +Ca 2+ +Mg 2+ in the equivalent proportion of 7:2:1 and found that stomatal conductance reduced quadratically with the increase in water salinity levels, at 180 days after sowing.…”
Section: Resultsmentioning
confidence: 99%
“…The quantitative and qualitative reduction of water sources has led to the search for strategies aimed at more efficient use of water, as well as rational use of waters considered of inferior quality since using saline water in agriculture is a necessity in semi-arid regions. In this context, several authors have studied the effect of irrigation with water of different salinity levels on the cultivation of guava (SOUZA et al, 2016;BEZERRA et al, 2018;XAVIER et al, 2022;LACERDA et al, 2022a); however, these studies are restricted to the use of waters with different levels of electrical conductivity, making it imperative to conduct new studies, particularly to assess the use of waters with different cationic natures on the guava crop in the seedling formation phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation